2003
DOI: 10.1007/s00424-003-1077-0
|View full text |Cite
|
Sign up to set email alerts
|

Predominant expression of Kv1.3 voltage-gated K+ channel subunit in rat prostate cancer cell lines: electrophysiological, pharmacological and molecular characterisation

Abstract: Voltage-gated K+ currents expressed in two rat prostate cancer ("Dunning") cell lines of markedly different metastatic ability were characterised using electrophysiological, pharmacological and molecular approaches. Whole-cell patch-clamp recordings showed that both strongly metastatic MAT-LyLu and weakly metastatic AT-2 cell lines possessed outward (delayed-rectifier type) K+ currents, which activated at around -40 mV. From the parameters measured, several characteristics of the two cell lines were similar. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 54 publications
(97 reference statements)
1
30
0
2
Order By: Relevance
“…1A). The expression levels of several other potassium channels previously shown to be up-regulated in cancers were either significantly decreased (TASK3 [Mu et al 2003], BK [Liu et al 2002;Bloch et al 2007], GIRK1 [Stringer et al 2001]) or unchanged (Kv1.3 [Fraser et al 2003]) ( Fig. 1A; Supplemental Fig.…”
Section: Eag2 Is Highly Up-regulated In Shh-driven Mouse Mbsmentioning
confidence: 90%
“…1A). The expression levels of several other potassium channels previously shown to be up-regulated in cancers were either significantly decreased (TASK3 [Mu et al 2003], BK [Liu et al 2002;Bloch et al 2007], GIRK1 [Stringer et al 2001]) or unchanged (Kv1.3 [Fraser et al 2003]) ( Fig. 1A; Supplemental Fig.…”
Section: Eag2 Is Highly Up-regulated In Shh-driven Mouse Mbsmentioning
confidence: 90%
“…Ion channels, including K þ channels, are important for cell cycle and cell proliferation and are found in a variety of cancer cells (Nilius and Wohlrab, 1992;Skryma et al, 1997;Ouadid-Ahidouch et al, 2000;Fraser et al, 2003;Parihar et al, 2003;Farias et al, 2004;Jager et al, 2004). It has been shown that K þ channels play a role in controlling proliferation and transformation of epithelial cells (Pardo et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Facilitation of K þ efflux by K þ -channel openers, (minoxidil, 1-ethyl-2-benzimidazolinone (EBIO), or diazoxide) was able to increase growth of PC-3 cells by 30-50%, whereas K þ -channel inhibitors (dequalinium, amiodarone, and glibenclamide) caused a dosedependent, growth inhibition of both androgen-sensitive (LNCaP, MDA-PCA-2B) and androgen-insensitive (PC-3, DU-145) human PCa cell lines. 15 The same blockers induced PC-3 apoptosis within 4 h treatment. 15 Thus, we can conclude that PCa epithelial cells that preserve androgen sensitivity, and display relatively weak metastatic potential, are generally characterized by higher I K and K þ -channel expression.…”
Section: Potassium Channelsmentioning
confidence: 97%
“…The existing data suggests that K v 1.3 is the dominant K vclass channel expressed in normal and cancerous rat and human prostate tissues, as well as in prostatic cell lines with different metastatic potentials, with lesser contributions from K v 1.4 and K v 1.6. [14][15][16] The difference between strongly metastatic rat MAT-LyLu and weakly metastatic AT-2 cell lines was again mostly found with regard to I K density, rather than biophysical properties. 16 This is consistent with the altered expression of the same channel types as opposed to the appearance of new ones.…”
Section: Potassium Channelsmentioning
confidence: 98%